Impact of lactate on immune cell function in the tumor microenvironment: mechanisms and therapeutic perspectives - Xuan-Yu Gu; Jia-Li Yang; Rui Lai; Zheng-Jun Zhou; Dan Tang; Dan Tang; Dan Tang; Long Hu; Li-Jin Zhao (Frontiers in Immunology)
Lactate has emerged as a key regulator in the tumor microenvironment (TME), influencing both tumor progression and immune dynamics. As a byproduct of aerobic glycolysis, lactate satisfies the metabolic needs of proliferating tumor cells while reshaping the TME to facilitate immune evasion. Elevated lactate levels inhibit effector immune cells such as CD8+ T and natural killer cells, while supporting immunosuppressive cells, such as regulatory T cells and myeloid-derived suppressor cells, thus fostering an immunosuppressive environment. Lactate promotes epigenetic reprogramming, stabilizes hypoxia-inducible factor-1α, and activates nuclear factor kappa B, leading to further immunological dysfunction. In this review, we examined the role of lactate in metabolic reprogramming, immune suppression, and treatment resistance. We also discuss promising therapeutic strategies targeting lactate metabolism, including lactate dehydrogenase inhibitors, monocarboxylate transporter inhibitors, and TME neutralization methods, all of which can restore immune function and enhance immunotherapy outcomes. By highlighting recent advances, this review provides a theoretical foundation for integrating lactate-targeted therapies into clinical practice. We also highlight the potential synergy between these therapies and current immunotherapeutic strategies, providing new avenues for addressing TME-related challenges and improving outcomes for patients with cancer.